Brutalist Non‐naturalism and Hume's Principle. (22nd January 2019) - Zangwill, Nick
Abstract: I argue that non‐naturalist moral realism does not have a problem with supervenience. The necessities may be explained as flowing from the essence of moral properties. It is still true that non‐naturalism embraces necessary connections between distinct things, thus offending against 'Hume's Principle' according to which there are no such connections. Therefore, the apparent appeal of Hume's principle needs addressing. Hume's Principle faces a tsunami of counterexamples, of both abstract and non‐abstract kinds of things. Furthermore, Hume's Principle lacks any motivation and is highly revisionary of ordinary modal thought. Not only are supervenience objections to non‐naturalism that draw on Hume's principle ineffective, but also the modal presuppositions of the supervenience argument are far stranger than anything in non‐naturalism.